The genesis, viability and effectiveness of community organizations the case of Pangasinan credit cooperatives - Legaspi, Perla E. (Philippine Journal of Public Administration, 1990)
Six Pangasinan credit cooperatives are assessed in terms of the relationship between their genesis, viability and effectiveness. The findings of the study indeed reveal that the manner of formation of the cooperatives, that is, whether they are initiated by the government or not, as well as the quality of the institution-building efforts put into these organizations largely determine their viability and effectiveness. Moreover, the study also yields some interesting insights on the initiation process, the role of the change agent and the concept of participation. Finally, the study offers a redesigned model of mobilizing people participation through community organizations, as well as proposals to improve the government's performance in community organizing and its partnership with non-governmental organizations in local development.